2009
DOI: 10.1021/je900599q
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Phenanthrene in Binary Mixtures of C1−C4 Alcohols at 298.2 K

Abstract: Experimental solubilities are reported for phenanthrene in binary solvent mixtures of methanol + 1-propanol, methanol + 1-butanol, ethanol + 1-propanol, ethanol + 1-butanol, and 1-propanol + 1-butanol at 298.2 K. Results of these measurements were used to evaluate the prediction capability of previously developed quantitative structure-property relationships employing the solubility data in monosolvents and the mean deviations (MDs) of the models' predicted values from the measured data varied between (1.7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Fakhree et al 78,79 measured the solubility of phenanthrene in binary solvent mixtures containing two alcohol solvents. The solvents included four primary alcohols (methanol, ethanol, 1-propanol, and 1-butanol) and one secondary alcohol (2-propanol).…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…Fakhree et al 78,79 measured the solubility of phenanthrene in binary solvent mixtures containing two alcohol solvents. The solvents included four primary alcohols (methanol, ethanol, 1-propanol, and 1-butanol) and one secondary alcohol (2-propanol).…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…Also, solubility amounts in studied monosolvents are in good agreement with previously published data. 6,7 Methanol (0.995 in mass fraction), ethanol (0.999 in mass fraction), 1-propanol (0.995 in mass fraction), and 1-butanol (0.995 in mass fraction) were purchased from Merck. A Karl Fischer titration method showed that the water contents of the solvents were 0.04%, 0.13%, 0.07%, 0.03%, and 0.30%, for methanol, ethanol, 1-propanol, 2-propanol, and 1-butanol, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…4 It is shown that these models can be applied to obtain calculated solubility data in binary mixtures of solvents with acceptable errors. [4][5][6][7] The J i coefficients are described as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation